2016
DOI: 10.1085/jgp.201611568
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct voltage-sensing domains control voltage sensitivity and kinetics of current activation in CaV1.1 calcium channels

Abstract: CaV1.1 is a slowly activating voltage-gated Ca2+ channel that exists in two splice variants with different voltage sensitivities. By making chimeras of these variants, Tuluc et al. show that activation kinetics and voltage dependence are controlled by distinct molecular mechanisms in the voltage-sensing domains of repeats I and IV, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 31 publications
(50 reference statements)
5
45
2
Order By: Relevance
“…In Ca V 1.2 and in Ca V 1.3 charge neutralization of D4 (D1327N, D1283N, respectively) caused a right-shift of V½ and a reduction of current density. Qualitatively these effects are consistent with the original observation in Ca V 1.1 [8,10] and suggest that, similarly to the situation in the skeletal muscle channel isoform, D4 in Ca V 1.2 and Ca V 1.3 might be involved in voltage sensor function and facilitate channel activation by serving as countercharge for the outer gating charges R1 and R2 in VSD IV. Previous structure modeling and mutagenesis analysis in Ca V 1.1 suggested that hydrogen bonds established between D4 and R1 during intermediate state 2 facilitate the transition into the activated state, resulting in the observed left-shifted V½.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In Ca V 1.2 and in Ca V 1.3 charge neutralization of D4 (D1327N, D1283N, respectively) caused a right-shift of V½ and a reduction of current density. Qualitatively these effects are consistent with the original observation in Ca V 1.1 [8,10] and suggest that, similarly to the situation in the skeletal muscle channel isoform, D4 in Ca V 1.2 and Ca V 1.3 might be involved in voltage sensor function and facilitate channel activation by serving as countercharge for the outer gating charges R1 and R2 in VSD IV. Previous structure modeling and mutagenesis analysis in Ca V 1.1 suggested that hydrogen bonds established between D4 and R1 during intermediate state 2 facilitate the transition into the activated state, resulting in the observed left-shifted V½.…”
Section: Discussionsupporting
confidence: 89%
“…Although in both Ca V 1.2 and Ca V 1.3 neutralization of D4 in the fourth VSD affected voltage-dependence of activation and peak current density, the magnitude of these effects was substantially smaller than that previously observed in Ca V 1.1 [8,10]. This could indicate that in Ca V 1.2 and Ca V 1.3 the putative D4-R1/R2 interaction is of minor importance for voltage-sensing, or it could indicate that the contribution of VSD IV to channel gating is smaller compared to Ca V 1.1.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations